Lactobacillus acidophilus induces virus immune defence genes in murine dendritic cells by a Toll-like receptor-2-dependent mechanism - Weiss, Gudrun (Blackwell Science Inc, 2010)
Lactobacilli are probiotics that, among other health-promoting effects, have been ascribed immunostimulating and virus-preventive properties. Certain Lactobacillus spp. have been shown to possess strong interleukin-12 (IL-12) -inducing properties. As IL-12 production depends on the up-regulation of type I interferons (IFNs), we hypothesized that the strong IL-12-inducing capacity of Lactobacillus acidophilus NCFM in murine bone-marrow-derived dendritic cells (DCs) is caused by an up-regulation of IFN-β, which subsequently induces IL-12 and the double-stranded RNA binding Toll-like receptor-3 (TLR-3). The expression of the genes encoding IFN-β, TLR-3, IL-12 and IL-10 in DCs upon stimulation with L. acidophilus NCFM was determined. Lactobacillus acidophilus NCFM induced a much stronger expression of Ifn-β, Il-12 and Il-10 compared with the synthetic double-stranded RNA ligand Poly I:C, whereas the levels of expressed Tlr-3 were similar. Whole genome microarray gene expression analysis revealed that other genes related to viral defence were significantly up-regulated and among the strongest induced genes in DCs stimulated with L. acidophilus NCFM. The ability to induce IFN-β was also detected in another L. acidophilus strain (X37), but was not a property of other probiotic strains tested, i.e. Bifidobacterium bifidum Z9 and Escherichia coli Nissle 1917. The IFN-β expression was markedly reduced in TLR-2(−/−) DCs, dependent on endocytosis, and the major cause of the induction of Il-12 and Tlr-3 in DCs stimulated with L. acidophilus NCFM. Collectively, our results reveal that certain lactobacilli trigger the expression of viral defence genes in DCs in a TLR-2 manner dependent on IFN-β.